2021
DOI: 10.3390/foods10081698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV-C Irradiation, Storage and Subsequent Cooking on Chemical Constituents of Fresh-Cut Potatoes

Abstract: UV-C irradiation successfully reduces the growth of microorganisms, but it can also affect the content of phenolics and sugars of fresh-cut potatoes (FCP). This could consequently alter antioxidant capacity of FCP or its potential for acrylamide formation. Therefore, this paper investigates the influence of UV-C irradiation on the content of phenolics [chlorogenic acid (CA)] and individual sugars during storage of FCP as well as after cooking. Acrylamide was also monitored in FCP after frying. Potato slices pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…Also, a similar study was performed by Pelaic et al. (2021), and the rise in sugar levels, especially evident after exposure to 5‐UV‐C irradiation, did not have an impact on the safety of the product in terms of acrylamide content. This is because all the fried samples remained below the maximum limit established by the EFSA and EU Commission Regulation, 2017/2158.…”
Section: Technologies For Reduction Of Acrylamidesupporting
confidence: 72%
See 1 more Smart Citation
“…Also, a similar study was performed by Pelaic et al. (2021), and the rise in sugar levels, especially evident after exposure to 5‐UV‐C irradiation, did not have an impact on the safety of the product in terms of acrylamide content. This is because all the fried samples remained below the maximum limit established by the EFSA and EU Commission Regulation, 2017/2158.…”
Section: Technologies For Reduction Of Acrylamidesupporting
confidence: 72%
“…But, the exposure of potato tubers to UV-C radiation resulted in a higher acrylamide content in the dry matter of products, as compared with the nonirradiated control specimen. Also, a similar study was performed by Pelaic et al (2021), and the rise in sugar levels, especially evident after exposure to 5-UV-C irradiation, did not have an impact on the safety of the product in terms of acrylamide content. This is because all the fried samples remained below the maximum limit established by the EFSA and EU Commission Regulation, 2017/2158.…”
Section: Uv and Gamma Irradiation Techniquesmentioning
confidence: 52%
“…The age of tubers also caused an increasing trend, but without statistical significance. Furthermore, the content of simple sugars and the acrylamide content in the fried samples increased with UV-C treatment of FCP, as reported by Pelaić et al (2021) [191]. However, in both studies, the acrylamide content in all samples was below the maximum level approved by the EFSA (750 µg/kg fresh weight).…”
Section: Acrylamidesupporting
confidence: 69%
“…The increased phenolic content can be stress-related (excessive UV light or wounding by minimal processing) [68]. On the contrary, Pelaić et al (2021) [191] observed a slight decrease in chlorogenic acid content, which was more expressed with higher applied doses. Some noticeable differences in the results in these studies are probably due to the application of different radiation doses and UV-C radiation conditions [171,189], different cultivars and minimal processing of potatoes and ultimately different packaging and storage of products.…”
Section: Uv-c Radiation and Its Effect On Fcpmentioning
confidence: 98%
See 1 more Smart Citation